Investigação sorológica, molecular e de marcadores genéticos de histocompatibilidade, na população de uma região endêmica, para leishmaniose tegumentar americana no sul do Brasil - Ribas-Silva, Rejane Cristina (2015)
We report the results of a serological and molecular research in individuals with no clinical manifestations of American cutaneous leishmaniasis (ACL) who lived in endemic area and we report the results of association between HLA class I genes (HLA-A, -B, and -C) and ACL in an endemic region of southern Brazil. A retrospective study was carried out on the epidemiological records of patients from the 13th and 15th Health Sections of the state of Paraná diagnosed with ACL. Patients with clinical manifestations of the disease and with positive parasite detection and/or Montenegro skin test were contacted for the collection of biological material and composition cases of group. The control group consisted of individuals with no clinical manifestations of ACL who lived in endemic region. Antibodies were detected in the healthy individuals by enzyme-linked immunosorbent assay (ELISA), and the positive samples were analyzed by indirect immunofluorescence (IIF) for Leishmania braziliensis and Trypanosoma cruzi. Polymerase chain reaction (PCR), employing the MP3H/MP1L primers, amplified a fragment of Leishmania (Viannia) k-DNA. All cases and controls group samples were subjected to HLA class I (HLA-A, -B, -C) typing were carried out through PCR-SSO using Luminex technology. The results reveal the presence of subclinical Leishmania infections and demonstrate the involvement of HLA-C*04 in the ACL susceptibility in individuals from an ACL-endemic region of southern Brazil.